Роль художньої літератури у формуванні читацької діяльності розумово відсталих учнів - Кравець, Ніна; Kravets, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто питання впливу художньої літератури на формування читацької діяльності у розумово відсталих учнів. Мета дослідження: визначити роль художньої літератури у формуванні читацької діяльності в розумово відсталих учнів. У дослідженні використано методи: статистичні, спостереження, педагогічний експеримент. Результати експерименту свідчать, що успішне оволодіння читацькою діяльністю розумово відсталими школярами залежить від належної організації роботи з літературними творами, що передбачає кілька етапів вивчення твору: підготовка до сприймання твору; сприймання твору; підготовка до аналізу твору; аналіз твору; підсумковий етап. На кожному з етапів доцільно використовувати як традиційні методи роботи з літературними творами: евристичний, творчого читання, репродуктивний, дослідницький, так і нетрадиційні, інноваційні технології навчання літератури: діалогові технології, літературні ігри, комп’ютерні технології, засоби підтримуючої й альтернативної комунікації тощо. Традиційні й нетрадиційні методи навчання літератури реалізуються в апараті організації засвоєння, поданому до кожного твору в підручнику з літератури. Твори художньої літератури за належної організації роботи з ними забезпечують оволодіння розумово відсталими учнями читацькою діяльністю. The article deals with the problems of literature fiction influence on the formation of mentally retarded pupils’ reading activity. The literature sources on this problem were analyzed. It is noted that the formation of skills and habits of reading activity to mentally retarded pupils is the most intense in the process of pupils’ work with literature fiction on the lessons of classroom and extracurricular reading. The results of the experiment suggest that successful mastery of mentally retarded students’ reading activities depends on the correct organization of work with the literary fictions foreseeing several stages of its learning, namely: preparation for perception of a work; perception of a work; preparation for the analysis of a work; analysis of a work; a final stage. At each stage it’s advisable to use traditional methods of work with literary fictions: heuristic, creative reading, reproductive, research, and non-traditional, innovative technologies of teaching literature: dialogue technology, literary games, computer technology, etc. Traditional and nontraditional methods of teaching literature are implemented in the apparatus of organization for assimilation, submitted to each work in the textbook of literature. Questions and tasks in the apparatus of organization for assimilation are diverse as they are designed for pupils with both higher and lower level of their cognitive capabilities development, for example: questions and tasks for establishing connections between phenomena and concepts that are studied, thanks to them the causal relationships can be determined; questions and tasks for revision and retention of educational material; questions of the heuristic orientation, stimulating mentally-speech activity of pupils; questions and tasks for self-control and self-independent work. Developing pupils’ bibliographic skills and habits is an important part of a reader’s activity. Consequently, literature fictions with proper organization of work with them ensure mastery of reading activities by mentally retarded pupils.
The role of fiction literature in the formation of mentally retarded pupil’s reading activity
Keywords: художня література; читацька діяльність; розумово відсталі учні; методи навчання літератури; інноваційні технології; етапи вивчення твору; fiction; readers activities; mentally retarded students; methods of literature teaching; innovative technologies; the phases studying of the work